Yield of staging laparoscopy before treatment of locally advanced pancreatic cancer to detect occult metastases. Issue 10 (October 2019) - Suker, M.; Koerkamp, B. Groot; Coene, P.P.; van der Harst, E.; Bonsing, B.A.; Vahrmeijer, A.L.; Mieog, J.S.D.; Swijnenburg, R.J.; Dwarkasing, R.S.; Roos, D.; van Eijck, C.H.J.
Abstract: Introduction: Locally advanced pancreatic cancer (LAPC) is found in 35% of patients with pancreatic cancer. However, these patients often have occult metastatic disease. Patients with occult metastases are unlikely to benefit from locoregional treatments. This study evaluated the yield of occult metastases during staging laparoscopy in patients with LAPC. Methods: Between January 2013 and January 2017 all patients with LAPC underwent a staging laparoscopy after a recent tri-phasic CT-scan of the chest and abdomen. Data were retrospectively reviewed from a prospectively maintained database. Univariate and multivariable logistic regression analysis was conducted to predict metastasis found at laparoscopy. Results: A total of 91 (41% male, median age 64 years) LAPC patients were included. The median time between CT-scan and staging laparoscopy was 21 days. During staging laparoscopy metastases were found in 17 patients (19%, 95% CI: 12%–28%). Seven (8%) patients had liver-only, 9 (10%) patients peritoneal-only, and 1 (1%) patient both liver and peritoneal metastases. Univariate logistic regression analysis showed that CEA (OR 1.056, 95% CI 1.007–1.107, p = 0.02) was the only preoperative predictor for occult metastases. In a multivariable logistic regression analysis of the preoperative risk factors again only CEA was an independent predictor for occult metastatic disease (p = 0.03). Patients with a CEA above 5 μg/L had a risk of occult metastasis of 91%. FOLFIRINOX was given to 69 (76%) of the patients with a median number of cycles of 8. Subsequent radiotherapy was given to 44 (48%) patients after the FOLFIRINOX treatment. Six (14%) patients underwent a resection after FOLFIRINOX and radiotherapy. The overall 1-year survival was 53% in patients without occult metastasis versus 29% with occult metastasis (p = 0.11). The 1-year OS for patients that completed FOLFIRINOX and radiotherapy was 84%. Conclusion: The yield of staging laparoscopy for occult intrahepatic or peritoneal metastases in patients with locally advanced pancreatic cancer was 19%. Staging laparoscopy is recomended for patients with LAPC for accurate staging to determine optimal treatment.